Acid Rain: A Review - Yousif , Malath I.; Jaythoom , Roaa A.; Jaber , Noor Nadhim (American Journal of Biology and Natural Sciences, 2025)
Around the world, acid rain (AR) has a complex harmful impact on plants and produces a variety of other environmental problems. Several previous studies have examined the direct impact of AR or its depositional components on plant damage and performance. The indirect effects of AR on plants, which are mediated by soil microorganisms and the abiotic environment of the soil rhizosphere, have not been well investigated, acidic deposition affects not only the distribution, composition, abundance, function, and activity of microorganisms associated with plants, but also the dynamics of certain substances in the soil, which may be detrimental to plants. Therefore, the indirect effects (AR → soil and water → plants) require more attention. The AR-soil chemical characteristics-plants route shows how soil solute leaching and acidification by AR would lower the availability of vital nutrients and increase the availability of heavy metals for plants, impacting the carbon and nitrogen cycles was therefore covered in this review in addition explores the direct impacts of AR on plant performance, growth, and biomass allocations on a whole-plant scale.